2021
DOI: 10.1080/10717544.2021.1971796
|View full text |Cite
|
Sign up to set email alerts
|

Glutaraldehyde-crosslinked chitosan-polyethylene oxide nanofibers as a potential gastroretentive delivery system of nizatidine for augmented gastroprotective activity

Abstract: Nizatidine (NIZ), a histamine H 2 -receptor antagonist, is soluble and stable in the stomach, however, it exhibits a short half-life and a rapid clearance. Therefore, chitosan (CS) and polyethylene oxide (PEO) nanofibers (NFs) at different weight ratios were prepared by electrospinning and characterized. The selected uncrosslinked and glutaraldehyde-crosslinked NFs were investigated regarding floating, solid-state characteristics, in vitro release, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 47 publications
0
10
0
Order By: Relevance
“…Cheng et al [ 131 ] used chitosan-coated nanoparticles for insulin delivery and found that they exhibited a 16-fold increase in insulin AUC when compared to an oral solution, and roughly 80% of that of a subcutaneous injection of insulin. Abd El Hady et al [ 132 ] synthesized chitosan–polyethylene oxide nanofibers for nizatidine delivery and found that nanofibers with an 8:2 ratio of chitosan to polyethylene oxide showed the highest mucoadhesive strength (22.82 g/cm 2 ), as well as prolonged drug release when compared to control nanofibers.…”
Section: Mucoadhesive Drug Delivery Systemsmentioning
confidence: 99%
“…Cheng et al [ 131 ] used chitosan-coated nanoparticles for insulin delivery and found that they exhibited a 16-fold increase in insulin AUC when compared to an oral solution, and roughly 80% of that of a subcutaneous injection of insulin. Abd El Hady et al [ 132 ] synthesized chitosan–polyethylene oxide nanofibers for nizatidine delivery and found that nanofibers with an 8:2 ratio of chitosan to polyethylene oxide showed the highest mucoadhesive strength (22.82 g/cm 2 ), as well as prolonged drug release when compared to control nanofibers.…”
Section: Mucoadhesive Drug Delivery Systemsmentioning
confidence: 99%
“…The potential of cross-linked chitosan and PEO combinations in nanofibre preparation was also reported by Abd El Haby et al who, apart from in vitro and ex vivo characterisation, conducted an in vivo study in rats for the prepared nanofibres. The results demonstrated a robust gastroprotective activity of nizatidine that was significantly more potent when formulated in cross-linked nanofibres, compared to drug solution and uncross-linked nanofibres [209].…”
Section: Floating and Mucoadhesive Systemsmentioning
confidence: 93%
“…Then, the Petri dish was kept at 37 °C using a hot air incubator (IVYX Scientific 5L Incubator, USA). The swelling behavior was observed at predetermined time intervals: 15, 30, 45, 60, 75, 90, 105, 120 min, and 24 h. At each time, samples were removed carefully from the Petri dish and blotted off cautiously on tissue papers to remove the surface-adhered liquid droplets and reweighed to constant weight . The experiment was done in triplicate, and the mean values were calculated.…”
Section: Methodsmentioning
confidence: 99%
“…In Vitro Floating (Buoyancy) Test. In vitro floating and buoyancy studies were carried out for all selected four nanofibrous mats based on the technique explained by Abd El Hady et al 29 Nanofibrous mats (1 × 1 cm 2 ) were placed in a flask containing 100 mL of 0.1 N HCl (pH 1.2) at 37 °C. The time necessary for test samples to go from the bottom to the surface of dissolution medium was called floating lag time (FLT).…”
Section: Design Of Experimental (Doe) Definitive Screening Designmentioning
confidence: 99%